Kesediaan Kontraktor Terhadap Garis Panduan Keselamatan Dan Kesihatan Pekerjaan Di Industri Pembinaan - Badrulhisham, Nur Syafikah; Wee, Seow Ta (Research in Management of Technology and Business, 2020)
The use of safety guidelines is important and requires special attention by all parties, especially contractors. However, the incompetent contractor’s attitude and failure to perform the job safely, inexperienced and inadequate safety guidelines are also major contributors to the accident at the site. Therefore, this study seeks to identify contractors’ adherence to the Occupational Safety and Health Guidelines in the Construction Industry (Management) and to examine the role of contractors in improving the safety of construction workers in accordance with the Occupational Safety and Health Guidelines in the Construction Industry (Management). The methodology of this study was to use qualitative methods through interviews with contractors registered grade 7 through the Construction Industry Development Board of Malaysia (CIDB). For both of these objectives, content analysis of interview data was conducted on six (6) contractors in the construction industry. The results of the contractor’s compliance with the Occupational Safety and Health (Management) Guidelines indicate that guidelines are essential for the implementation of a construction project. This is because, the existing laws are not enough to address the problem and achieve the zero-sum goals at the construction site. While the findings of the contractor’s role in improving the safety of workers at the site found that all the respondents agreed and stated that the roles provided in the OSHCIM Guidelines were all fulfilled because the contractors were obliged to adhere to the guidelines provided. In conclusion, it is hoped that this study will be of benefit to those who undertake construction projects in Malaysia.